Microstructure and mechanical properties of laser butt welds of selective laser melted Ta10W alloy plates with different forming directions - Xin Du; Qiang Wu; Tong Zhang; Jianglin Zou; Rongshi Xiao; Haipeng Zhou; Ding Han; Tingyou Jiao (Journal of Materials Research and Technology, 2023)
This study investigates the anisotropy effect of Ta10W alloy manufactured by selective laser melting (SLM) on the microstructure and mechanical properties of the three butt welds. The welds were characterized by formation, microstructure, microhardness, room temperature (RT) strength, high temperature (HT) strength, and fracture morphology. Results indicate that Ta10W manufactured by SLM exhibits anisotropy in microstructure and properties, leading to notable differences in the welds' microstructure and mechanical properties. When the base metal's X-axis aligns with the welding direction, the weld forms columnar sub-grains, whereas aligning the base metal's Z-axis with the welding direction results in equiaxed sub-grains in the weld. These distinct microstructures influence the maximum RT strength, with the X + X weld displaying significantly higher strength (751.33 MPa) compared to the X + Z (672.00 MPa) and Z + Z (667.25 MPa) welds. Fracture analysis reveals a transition from cleavage fracture to intergranular fracture in three welds. The microhardness and HT strength of the welds exhibit an inapparent difference, with the microhardness of approximately 305 HV0.2/15 and the HT (1800 °C) strength of around 110.50 MPa.